Toward Seamless Shopping: A Bibliometric Journey of Unraveling UTAUT in the Digital Marketplace - Shafi, Sujana; Mohamed , Wan Norhayati; Damaianti, Indriana; Salleh, Hayatul Safrah (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The application of the Unified Theory of Acceptance and Use of Technology (UTAUT) in online shopping research has gained significant attention from scholars aiming to understand consumer behavior in digital retail environments. This study conducts a bibliometric analysis to systematically explore the literature on UTAUT in the context of online shopping. By examining bibliographic data from academic databases, the research investigates publication trends, authorship patterns, institutional affiliations, geographical distributions, document types, journal publications, citation patterns, keyword usage, bibliographic coupling networks, and key thematic formations. Using VOSviewer Version 1.16.20, the study identifies key research trends, influential authors and institutions, geographical hotspots, prominent journal publications, highly cited articles, frequently used keywords, and bibliographic coupling networks among authors, sources, themes, and countries. These findings contribute to shaping the application of UTAUT in online shopping. By synthesizing and visualizing these insights, this bibliometric analysis enhances understanding of how UTAUT has been utilized and studied in the online shopping domain, offering valuable perspectives for researchers, practitioners, and policymakers.